USING MEMORY GAMES IN TEACHING ENGLISH LEARNING (ResearchJet Journal of Analysis and Inventions, 2021)
This article is about using memory games in teaching English learning. In this article I would like to reflect how modern teachers evaluate the adequacy in using games when teaching English language. Using memory games as a key role in vocabulary learning and how the games can help learners recall material in a pleasant, entertaining way.